Determinan Pertumbuhan Ekonomi Provinsi yang Ada di Pulau Sumatera - Daffa Muzakki; Imam Kurniawan; Muhammad Ichwan; Muhammad Rifki Surya Pratama; Reno Andrian; Vanessa Septia Putri; M. Zulkarnain (Equivalent : Journal of Economic, Accounting and Management, 2025)
Abstract : The purpose of this study is to identify and analyze the components that influence the economic growth of Sumatra Island. The research method used to identify the components of economic growth in Sumatra Island is a quantitative approach supported by descriptive and inferential analysis. The results show that high unemployment rates and labor participation rates are positively related to economic growth in Sumatra Island. In addition, economic growth in Sumatra Island is also influenced by major sectors such as plantations, mining, and trade. Abstrak :   Tujuan penelitian ini adalah untuk mengidentifikasi dan menganalisis komponen yang memengaruhi pertumbuhan ekonomi Pulau Sumatera. Metode penelitian yang digunakan untuk mengidentifikasi komponen pertumbuhan ekonomi di Pulau Sumatera adalah pendekatan kuantitatif yang didukung oleh analisis deskriptif dan inferensial. Hasil menunjukkan tingkat pengangguran yang tinggi dan tingkat partisipasi tenaga kerja berhubungan positif dengan pertumbuhan ekonomi di Pulau Sumatera. Selain itu, pertumbuhan ekonomi di Pulau Sumatera juga dipengaruhi oleh sektor-sektor utama seperti perkebunan, pertambangan, dan perdagangan.